1997
DOI: 10.1086/515543
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Corticosteroid Therapy for Tuberculosis: A Critical Reappraisal of the Literature

Abstract: An extensive, although largely forgotten, literature addresses the utility of adjunctive corticosteroid therapy in the management of tuberculosis. Corticosteroid therapy probably improves neurological outcomes of, and decreases mortality due to, tuberculous meningitis of moderate severity. Although therapy for tuberculous pericarditis is simplified (with less need for operative intervention) by adjunctive corticosteroid administration and there are fewer deaths, the incidence of subsequent constriction is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
11

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(103 citation statements)
references
References 68 publications
1
91
0
11
Order By: Relevance
“…6 There has been no adequate evidence regarding the role of corticosteroid on acute disseminated tuberculosis. 10 Data on corticosteroid use in congenital tuberculosis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…6 There has been no adequate evidence regarding the role of corticosteroid on acute disseminated tuberculosis. 10 Data on corticosteroid use in congenital tuberculosis are very limited.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Disseminated TB is common in renal transplant patients, accounting for 40% of cases, 9 in marked contrast to the 0.6%-1.4% incidence in the general population. 18 Disseminated TB in these patients commonly presents as fever of unknown origin.…”
Section: Discussionmentioning
confidence: 99%
“…The role of adjunctive corticosteroid therapy in the treatment of TB meningitis has been investigated by numerous studies [52][53][54][55][56][57][58][59][60][61][62][63][64], and the updated systematic review conducted in support of the guidelines showed a mortality benefit from the use of adjuvant corticosteroids. Therefore, the guidelines recommend adjunctive corticosteroid therapy with dexamethasone or prednisolone tapered over 6-8 weeks for patients with TB meningitis (PICO question 8).…”
Section: Tb Meningitismentioning
confidence: 99%